The Use of Telemedicine Postoperative Visits Following Carpal Tunnel and Trigger Digit Releases: A Randomized Clinical Trial - Earp, Brandon E; Zhang, Dafang; Benavent, Kyra A; Ostergaard, Peter J; Blazar, Philip E (The Journal of hand surgery (American ed.), 2025)
Virtual visits have become increasingly popular in North American health care. This study assessed differences in patient-reported outcome measures, satisfaction, travel costs, and complication rates between patients who had either virtual video-based or in-person 2-week postoperative visits after undergoing carpal tunnel release (CTR) or trigger digit release (TDR). We performed a prospective, randomized trial of patients who underwent isolated TDR or CTR. Subjects were randomized to receive their 2-week postoperative visit via a virtual video-based platform or an in-person visit. All patients received the same immediate postoperative care instructions. Our primary outcome variable was Press Ganey Outpatient Medical Practice Survey (PG) score at 2 weeks after surgery. Secondary outcomes included PG score at 3 months after surgery, and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) at 2 weeks and 3 months after surgery. Demographics, complications, and patient expenses were collected. Sixty subjects were randomized with 30 in each group. The average age was 59 years, 40 subjects were women, and 35 subjects underwent CTR. The median 2-week PG in the in-person group was 4.7 and 4.1 in the virtual visit group. This was a statistically significant difference; however, there was no difference at the 3-month visit. Male sex and older age were significantly associated with lower PG scores at 3 months after surgery. There was no difference in QuickDASH at either time point. The virtual visit follow-up group had significantly fewer hours off work, lower transportation costs, and less travel distance. Although overall patient satisfaction is high following CTR and TDR, a lower self-reported patient satisfaction was seen in the virtual visit group as compared with the in-person group at 2 weeks, which equalized by 3 months. Individualized discussions with patients about postoperative visit options that factor in cost and travel may optimize the patient experience.